POPULASI KUMBANG TANDUK (Oryctes rhinoceros L.) PADA KEBUN KELAPA SAWIT PEREMAJAAN SISTEM SISIPAN DAN TUMBANG SEREMPAK DI KECAMATAN BAHAR UTARA KABUPATEN MUARO JAMBI - Hayata Hayata; Nasamsir Nasamsir; Beni Afriansyah (Jurnal Media Pertanian, 2021)
It is necessary to carry out replanting  activities  to increase  the production and productivity of oil palm plants.  Rejuvenation of oil palm plantations can be done through an inserting system  and totally rejuvenation system. The population propagation of horn beetles  growed faster  in oil palm plantations with inserting rejuvenation system than in totally rejuvenation system. This study aimed to obtain an accurate information on the population of horn beetles in oil palm plantations. The research has been conducted on  July-August 2020  in Talang Bukit Village as an inserting system area Talang Datar Village as a totally rejuvenation area, Bahar Utara District, Muaro Jambi Regency, Jambi Province. An unformated trial was carried out as an experimental design and the location determination was purposively chosen  for there were plants under study and showed a uniform condition at that location.  the sampling locations based on oil palm plantation rejuvenation systems, namely: (1) inserting rejuvenation system, and (2) totally rejuvenation system. There were 15 / Ha population at oil palm plantation with inserting rejuvenation system,  while there were 3 horn beetles/Ha in totally rejuvenation system. The percentage of horn beetle attacking was 22,22 in  inserting rejuvenation system while it was only 3.70%. in the  totally rejuvenation system.Key words: population, horn beetle,  rejuvenation, oil palm